Developing Genre Awareness in Medical Translation Training – Introducing a Genre Typology and Translation Guide - Horváth, Ágnes (Working Papers in Language Pedagogy, 2021)
As conscious language users and mediators, translators should understand that every text belongs to a certain genre and that every genre has its own rules and conventions. Otherwise, the result can be a text the target audience finds odd. To raise medical translators’ awareness of this problem, genre studies should be included in their training. However, as there are numerous genres of medical document, Semmelweis University’s medical translator training aims to develop students’ genre awareness and text analysis skills by providing them with a typology that allows them to discover the characteristics of any genre in a systematic way and make appropriate decisions in the process of translation. In this practitioner research, I present courses and tasks that contribute to trainee translators’ genre awareness building in medical translation. More specifically, I propose a genre typology based on a translation-oriented text analysis that helps trainees map genre characteristics and formulate adequate translation strategies. A translation guide is also put forward, which comes from the idea of the translation brief, that may serve as both a manual during the translation process and as a tool for measuring translation quality.